Autonomy, Positive Relationships, and IL-6: Evidence for Gender-Specific Effects - Eisenlohr-Moul, Tory A. (2012)
OBJECTIVES: A body of evidence indicates that women value relationship-centered aspects of well-being more than men do, while men value autonomy-centered aspects of well-being more than women do. The current study examined whether gender moderates relations between autonomy and positive relationships and interleukin-6 (IL-6), a cytokine associated with inflammatory processes. Aspects of well-being consistent with gender-linked values were expected to be most health-protective such that positive relationships would predict lower IL-6 only or more strongly in women, and autonomy would predict lower IL-6 only or more strongly in men. METHODS: In the first study, a sample of 119 older adults (55% female) living in Kentucky were visited in their homes for interviews and blood draws. In the second study, a sample of 1,028 adults (45% female) living across the United States (U.S.) underwent a telephone interview followed by a visit to a research center for blood draws. RESULTS: In the Kentucky sample, autonomy was quadratically related to IL-6 such that average autonomy predicted higher IL-6; this effect was stronger in men, providing support for our hypothesis only at above average levels of IL-6. In the U.S. national sample, more positive relationships were associated with lower IL-6 in women only. When the national sample was restricted to match the Kentucky sample, higher autonomy was associated with lower IL-6 in men only. CONCLUSIONS: Results provide preliminary evidence for gender-specific effects of positive relationships and autonomy on IL-6. Further work is needed to establish the generalizability of these effects to different ages, cultures, and health statuses.